Comrades in Arms: Masculinity and Recollections of the First World War in the Texts of Czechoslovak K.u.K. War Veterans - Hutečka, Jiří (Dějiny – teorie – kritika, 2014)
The article aims at analysing the process of remembering and memory discourses of the First World War as experienced by Czech and Slovak veterans during the interwar years. The main focus is on the vast majority of Czech ex-servicemen who spent the war in Austro-Hungarian uniform. In the new Czechoslovak state, their war recollections were thus in a somewhat precarious position. Th ey had to cope with the fact that the years they spent in the trenches were not only completely overshadowed by the offi cial discourse of the ‘heroic legionnaire’ (i.e., member of the Czechoslovak Legion, a small minority of men who served in the war), but also with the fact that since the early 1920s the general Czechoslovak society sought to construct its (non-legionary) memory of the war around the increasingly prominent concept of the ‘good soldier Svejk’, i.e., a slacker subversive to the K.u.K. war eff ort, permanently waiting to go AWOL. Since the hegemonic masculinity of the time tended to at least partially revolve around the image of heroic service (epitomized by the legionnaire myth), the author follows several paths which the K.u.K. exservicemen took in their eff ort to both fi t into the general discourse of wartime ‘nation building’ and to keep in line with the hegemonic masculine image. It becomes clear that after the Great Depression and especially during 1930s, their efforts in this area resulted in a group-specific collective memory of the First World War which emphasised that, although unwillingly, they performed their duty well as befi ts good men and good citizens.